2009
DOI: 10.1093/annonc/mdn682
|View full text |Cite
|
Sign up to set email alerts
|

Survival among women with triple receptor-negative breast cancer and brain metastases

Abstract: In this single-institutional study, patients with nonmetastatic triple receptor-negative breast tumors have a high early incidence of brain metastases associated with poor survival and maybe an ideal cohort to target brain metastases preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
75
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(84 citation statements)
references
References 23 publications
6
75
1
2
Order By: Relevance
“…Brain metastases has been thought to be more common with TNBC patients risk being 6-46% [20][21][22]of those experiencing metastatic disease, we had one patient with multiple brain metastases who received palliative radiotherapy but later succumbed to death within 4 months of diagnosing brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Brain metastases has been thought to be more common with TNBC patients risk being 6-46% [20][21][22]of those experiencing metastatic disease, we had one patient with multiple brain metastases who received palliative radiotherapy but later succumbed to death within 4 months of diagnosing brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this finding, recent reports have demonstrated that molecular subtypes of breast cancer other than HER2-positive disease (eg, triple-negative tumors) may be related to an increased risk of CNS metastases independently of treatment-related factors. 46,47 The current study is inherently limited by its observational nature. Because of this, it is supposed that the treatment with trastuzumab was not randomly allocated among HER2-positive patients but was determined depending on the patient status.…”
Section: Discussionmentioning
confidence: 99%
“…(3,4) However, the incidence and survival from BM in this cohort has yet to be well-defined. (7)(8)(9) We noted that, among women with TNBC, BM occurs …”
Section: Clinical Outcome According To Breast Cancer Subtypesmentioning
confidence: 99%